2000
DOI: 10.1046/j.1463-5224.2000.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Cochet-Bonnet aesthesiometer-determined corneal sensitivity in neonatal foals and adult horses

Abstract: Corneal touch threshold (CTT) was measured in sick neonatal foals, healthy foals, and healthy adult horses with a Cochet-Bonnet aesthesiometer. The mean overall CTT for the adult horses, sick foals, and healthy foals was 4.82 +/- 0.87 cm, 3.21 +/- 0.24 cm, and 5.01 +/- 0.61 cm, respectively. The central cornea of adult horses was more sensitive than the limbal cornea. Corneal sensitivity was significantly reduced in sick neonatal foals compared to adults. The mean Schirmer I tear test values were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
105
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(119 citation statements)
references
References 0 publications
11
105
1
2
Order By: Relevance
“…The mean baseline corneal sensitivity (determined via CTT measurement) did not vary significantly among drug solution treatments within a given experimental group (the completely randomized design experimental group or the replicated Latin square experimental group); baseline CTT values ranged from 2.9 to 3.9 cm, which is in accordance with results of previous studies [7][8][9][10]22 in horses that were evaluated by use of the same type of aesthesiometer. After treatment administration, CTT values differed significantly from the respective baseline value for some time, depending on drug solution; among the drug solutions, significant differences in CTT values were detected at various time points after application.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The mean baseline corneal sensitivity (determined via CTT measurement) did not vary significantly among drug solution treatments within a given experimental group (the completely randomized design experimental group or the replicated Latin square experimental group); baseline CTT values ranged from 2.9 to 3.9 cm, which is in accordance with results of previous studies [7][8][9][10]22 in horses that were evaluated by use of the same type of aesthesiometer. After treatment administration, CTT values differed significantly from the respective baseline value for some time, depending on drug solution; among the drug solutions, significant differences in CTT values were detected at various time points after application.…”
Section: Discussionsupporting
confidence: 85%
“…6 The CTT has been studied as a measure of corneal sensitivity in horses of various ages and breeds, and its mean value has been reported to range from 2.12 ± 0.62 cm to 5.01 ± 0.61 cm as determined by use of the Cochet-Bonnet corneal aesthesiometer. [7][8][9][10] Previous studies 7,9 in horses have revealed that the central portion of cornea is the most sensitive, followed in order of decreasing sensitivity by the nasal, temporal, ventral, and dorsal regions. It is presumed that these location-related differences in corneal sensitivity reflect the relative abundance in nerve fiber density at these locations because the central portion of the cornea in other animals has the greatest corneal nerve fiber density.…”
mentioning
confidence: 99%
“…Moreover, this information is similar to those reported by Blocker and Van Der Woerdt (2001) in cats and by Brooks et al (2000) in horses. Barret et al (1991) and Herring et al (2005) observed that dolichocephalic dogs exhibit esthesiometry values of 1.75cm, similar to the results obtained in this study (1.7cm).…”
Section: Arqsupporting
confidence: 90%
“…Corneal sensitivity has alert function for possible injuries or diseases (BROOKS et al, 2000). In horses, the sensitivity values are higher compared to other animals such as dogs and cattle (KAPS et al, 2003;WIESER et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It can be affected by several factors, including the skull anatomy and orbit that change the positioning and insertion of the eyeball in each breed, ambient temperature and humidity and age of the individual (LACERDA et al, 2014;MONÇÃO-SILVA et al, 2016). Factors that may influence the corneal touch threshold (CTT) values have already been studied in horses (BROOKS et al, 2000;KAPS et al, 2003;WIESER et al, 2013), birds (LACERDA et al, 2014), dogs (KOBASHIGAWA et al, 2015) and cats (BLOCKER & VAN DER WOERT, 2001). However, studies that addressed the mechanism and values of corneal sensitivity in horses are scarce, and when carried out, data were reported without breed subdivision (BROOKS et al, 2001;KAPS et al, 2003;WIESER et al, 2013).…”
Section: Introductionmentioning
confidence: 99%